Artificial intelligence, opportunities and limitations of its use in education - E. N. Tkachenko (Путеводитель предпринимателя)
The article considers the problem of using artificial intelligence (AI) technologies in the educational process. Based on a review of foreign scientific publications, the author defines the essence of artificial intelligence, the opportunities that it provides to both teachers and students in the framework of educational practice. It is noted that competencies in the field of artificial intelligence have become one of the important technological skills of the twenty–first century. Having competencies in the field of artificial intelligence, people can critically evaluate digital technologies in general, communicate and collaborate effectively with their help, as well as use them as a tool in the workplace and at home.The author presents and analyzes the European structure of digital competence of teachers based on the DigCompEdu platform.It is concluded that artificial intelligence can facilitate the work of teachers, and students can creatively solve educational problems. At the same time, teachers need to improve their pedagogical and technological competence in order to create appropriate learning conditions that make it possible to maximize the benefits that artificial intelligence provides.